Entomofauna present in plant shelters in a vineyard var. Crimson Seedless in Ica-Peru - Narrea-Cango, Mónica; Gómez, Luz (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2024)
The use of chemical pesticides to control pests also affects beneficial insects, so it is necessary to implement mechanisms that allow them to be protected and promote their development. In the present investigation, three plant shelters were installed to identify their entomofauna and determine the plant species with the potential to host biological controllers of grapevine pests. The study was carried out in the 2020-21 growing season, with seven plant species to make up three plant shelters (A, B, and C) that were installed on the edges of a vineyard of the Crimson Seedless variety in Ica, Peru. In total, 1,209 insects were reported, in six orders, nine families, and sixteen species; the most abundant were pollinators, followed by phytophagous, predators, and some parasitoids. There were no statistical differences between the shelters in terms of the abundance of parasitoids and pollinators, but there were in predators and phytophagous specifically between shelters A and B with C. Shelters A and B, which included the fennel Foeniculum vulgare Mill., stood out for having a larger population of predators, including Chrysoperla externa (Hagen), the main controller of the “vine mealybug” (Planococcus spp.). The importance of plant shelters was demonstrated and their implementation in vineyards is recommended to promote biological control and contribute to integrated pest management in this crop.